Investigating the history of psychology: methodological contributions - Ana Maria Jacó-Vilela; Adriana Amaral do Espírito-Santo; Filipe Degani-Carneiro; Lidiane de Oliveira Goes; Maira Allucham Goulart Naves Trevisan Vasconcellos (Interacciones)
This article aims to present methodological discussions about the research on the History of Psychology. Here it is used as a guiding axis in the comprehension of history, methodological and theoretical perspectives of the New History. In its critical to the traditional history, the New History proposes the analysis of the conditions of construction of the narratives about the facts. One of its consequences was the expansion of the historical document field, with the utilization of other sources, different than official texts. In the History of Psychology, that expansion meant the concern about the scientific type of historical researches and the considerations about the ways of thinking and making Psychology, considering the context and the voices of those who helped to build it as knowledge and professional practice. In the case of Brazil, different initiatives and laboratories have reaffirmed the importance of the debate about the systematic organization and the careful analysis of the research material. Some examples are referred here, so as to demonstrate this kind of proposal.